Metal battery composite diaphragm as well as preparation method and application thereof
By wrapping the conductive layer and insulating layer on both sides of the metal battery separator base, the interface electric field and thermal field are regulated, the safety hazards caused by dendrites are solved, the stability and safety of the separator are improved, and the cycle life of the battery is extended.
Patent Information
- Application Number
- CN202411383777.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-20
AI Technical Summary
During multiple or large-scale charging and discharging of metal batteries, due to the uneven distribution of active ions and charges, dendrites are generated and pierced through the diaphragm, causing safety hazards.
The nano-thick conductive layer and insulating layer are wrapped in both sides of the commercial diaphragm matrix in turn. The electric field and heat field of the diaphragm/electrolyte/electrode interface are regulated through the conductive layer, and the uniform distribution of active ions and charges is achieved, dendrites are inhibited, and dendrites are inhibited, and the electrical insulation is passed through the conductive layer. The layer prevents the electrons from short-circuiting with the positive and negative electrodes.
It improves the stability and safety of the diaphragm, extends the cycle life of the battery, reduces the risk of the diaphragm being pierced, and improves the Coulomb efficiency and safety of the battery.
Smart Images

Figure CN119171010A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal battery separators, and in particular relates to a metal battery composite separator and a preparation method and application thereof. Background Art
[0002] With the excessive consumption of traditional fossil energy and the rapid development of new energy, matching technologies such as batteries, supercapacitors, fuel cells, water electrolysis or cracking to produce hydrogen fuel and carbon dioxide electrochemical energy storage and conversion technologies have developed rapidly. In energy conversion and storage systems, metal batteries are recognized as one of the most efficient and labor-saving energy utilization devices in portable electronic devices, electric vehicles and fixed power stations. Due to the high energy density and long cycle life of metal batteries, the demand for metal batteries in practical applications is increasing. Metal batteries will develop in the direction of high specific capacity, higher power, high charge and discharge efficiency, high cycle performance and lower cost. Whether it is to optimize and improve the mature lithium-ion batteries currently in use, or to study and design new post-lithium energy storage batteries such as sodium, potassium, magnesium, zinc, calcium and aluminum, they have attracted much attention.
[0003] The safety of metal batteries depends to a large extent on the stability and safety of the diaphragm. At present, during multiple or high-rate charge and discharge processes, the uneven distribution of active ions and charges on the metal negative electrode surface of metal batteries causes uneven metal deposition and stripping reactions. Coupled with the increasingly strong "tip effect", the formation of dendrites is triggered and eventually pierces the diaphragm, resulting in micro-short circuits and safety hazards. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a metal battery composite diaphragm and its preparation method and application. The present invention sequentially wraps a conductive layer and an insulating layer on both sides of a commercial diaphragm substrate, and uniformly regulates the electric field and thermal field of the diaphragm / electrolyte / electrode interface through the conductive layer, thereby improving the kinetics while uniformly distributing active ions and charges, inhibiting the uncontrollable growth of dendrites, and the insulating layer is used to prevent positive and negative electrode electronic short circuits, thereby improving the safety and stability of the diaphragm.
[0005] The present invention is specifically implemented through the following scheme.
[0006] The present invention provides a metal battery composite diaphragm, comprising a diaphragm substrate, a conductive layer and an insulating layer, wherein the conductive layers are deposited on both sides of the diaphragm substrate, and the insulating layer is deposited on the outer side of the conductive layer;
[0007] The conductive layer is one of TiN, MoN, SnO2, ITO, Al, Sn, Fe, Zn, Pt, Ni, Cu, Co, Au, Ag, Pb, Ti, Mo, and C; preferably one of TiN, MoN, SnO2, ITO, AlMo, and C;
[0008] The insulating layer is one of Al2O3, ZrO2, TiO2, HfO2, SiO2, BN, C3N4, BaTiO3, SrTiO3, and Si, preferably one of Al2O3, TiO2, SiO2, BN, and BaTiO3.
[0009] The thickness of the conductive layer is 1nm to 50nm, and the thickness of the insulating layer is 1nm to 50nm. If the conductive layer is too thin, the uniform electric field capability is weak. If the conductive layer is too thick, it will cause pore blockage or powder loss. If the insulating layer is too thin, the conductive layer is easily exposed, resulting in short circuit due to electronic conductivity of the diaphragm. If it is too thick, it will cause pore blockage or powder loss.
[0010] In a preferred embodiment of the present invention, the membrane matrix is selected from commercial porous polymer base membranes, specifically selected from polypropylene (PP), polyethylene (PE), PP / PE / PP, cellulose membranes, polytetrafluoroethylene (PTFE), PES, glass fiber, cellulose filter membranes, A4 paper, facial tissue, and weighing paper.
[0011] The present invention provides a method for preparing the above-mentioned metal battery composite diaphragm, comprising the following steps:
[0012] The membrane substrate is washed and then dried; the preferred method is to place the commercial porous polymer substrate membrane in a washing solution and vacuum dry it, the drying temperature is 60°C to 200°C, and the drying time is 10h to 24h;
[0013] Using atomic layer deposition (ALD), physical vapor deposition (PVD), chemical vapor deposition (CVD) or magnetron sputtering, a conductive layer is first deposited on both sides of the treated membrane substrate to obtain a conductive modified membrane;
[0014] An insulating layer is deposited on the outer side of the conductive modified diaphragm by atomic layer deposition, physical vapor deposition, chemical vapor deposition or magnetron sputtering to obtain a metal battery composite diaphragm that can inhibit dendrite growth.
[0015] In a preferred embodiment of the present invention, an atomic layer deposition method is used to deposit a conductive layer on both sides of the treated membrane substrate to obtain a conductive modified membrane, wherein the conductive layer is one of TiN, MoN, SnO2 or ITO; preferably SnO2, TiN, MoN.
[0016] A conductive modified diaphragm is obtained by depositing a conductive layer on both sides of the treated diaphragm substrate using a physical vapor deposition method, wherein the conductive layer is Al, Sn, Fe, Zn, Pt, Ni, Cu, Co, Au, Ag, Pb, Ti, Mo, TiN, MoN, SnO2 or ITO; preferably Al, TiN, and ITO.
[0017] A conductive modified diaphragm is obtained by depositing a conductive layer on both sides of the treated diaphragm substrate using a chemical vapor deposition method, wherein the conductive layer is one of C, Al, Mo, SnO2, TiN, and ITO; preferably SnO2, Mo, and TiN.
[0018] A conductive modified diaphragm is obtained by depositing a conductive layer on both sides of the treated diaphragm substrate using a magnetron sputtering method, wherein the conductive layer is C, Al, Sn, Fe, Zn, Pt, Ni, Cu, Co, Au, Ag, Pb, Ti, Mo, TiN, MoN, SnO2 or ITO; preferably C, ITO, TiN.
[0019] An insulating layer is deposited on the outer side of a conductive modified diaphragm using atomic layer deposition to obtain a metal battery composite diaphragm that can inhibit dendrite growth, wherein the insulating layer is Al2O3, ZrO2, TiO2, HfO2, SiO2, BN, C3N4, BaTiO3 or SrTiO3; preferably TiO2, BaTiO3, and BN.
[0020] A metal battery composite membrane capable of inhibiting dendrite growth is obtained by depositing an insulating layer on the outer side of a conductive modified membrane using physical vapor deposition, wherein the insulating layer is Si, Al2O3, ZrO2, TiO2, HfO2, SiO2, BN, C3N4, BaTiO3 or SrTiO3; preferably Al2O3, BN, BaTiO3.
[0021] An insulating layer is deposited on the outer side of a conductive modified diaphragm using chemical vapor deposition to obtain a metal battery composite diaphragm that can inhibit dendrite growth, wherein the insulating layer is Al2O3, ZrO2, TiO2, SiO2, HfO2, BN, C3N4, BaTiO3 or SrTiO3; preferably SiO2, TiO2, BN.
[0022] An insulating layer is deposited on the outer side of the conductive modified diaphragm using magnetron sputtering, wherein the insulating layer is Si, Al2O3, ZrO2, TiO2, SiO2, BN, C3N4, BaTiO3 or SrTiO3; preferably SiO2, BaTiO3, BN.
[0023] In a preferred embodiment of the present invention, the process of depositing a conductive layer on both sides of a commercial porous polymer substrate using an atomic layer deposition method comprises the following steps:
[0024] The precursors of TiN, MoN, SnO2 or ITO that react to form a conductive layer are introduced into the reaction chamber of an atomic layer deposition instrument to deposit a conductive layer. The precursors include precursor A and precursor B. Specifically, an atomic layer deposition instrument is used and Ti(NEt2)4, Cp * TiCl3、Cp *Ti(NMe2)3, CpTi(NMe2)3, Ti(NMe2)4, Ti( i PrO)4、Ti(NMeEt)4、Cp * Ti(OMe)3, TTIP, TiCl4, Ti(OMe)4, C8H 24 N2Ti, Ti(Me5Cp)(OMe)3, Mo(CO)6, MoCHT(CO)3, Mo(NtBu)2(NMe2)2, Mo(CO)4(CH3CN)2, Mo(CO)3(NCCH2CH3)3, (NH3)3Mo(CO)3, Mo(CO)3(C7H8), MoCl5, C8H 24 N4Sn, Sn(OtBu)4, SnCl4, InCp, InMe3, C 15 H 21 InO6, In(thd)3, C 15 H 12 One or more of F9InO6 and InCl3 are used as precursor A, and one of NH3, O3 and H2O is used as precursor B to deposit a conductive layer; wherein the sputtering atmosphere is a nitrogen or argon atmosphere, the carrier gas flow rate is 30sccm~800sccm, the precursor introduction time is 0.1s~60s, the diffusion time is 0.1s~60s, and the growth temperature is 100℃~1000℃.
[0025] In a preferred embodiment of the present invention, the process of depositing a conductive layer on both sides of a commercial porous polymer substrate film using a physical vapor deposition method comprises the following steps:
[0026] A physical vapor deposition apparatus is used and Al, Sn, Fe, Zn, Pt, Ni, Cu, Co, Au, Ag, Pb, Ti, Mo, TiN, MoN, SnO2 or ITO is used as the coating material, argon is introduced as the protective gas, the deposition temperature is 200°C to 650°C, the deposition time is 60 to 600 min, the deposition rate is about 0.2 nm / s to 2 nm / s, the deposition bias is preferably 25 V to 100 V, the power is preferably 100 W to 200 W, the sputtering bias is preferably 25 V to 120 V, and the sputtering pressure is preferably 0.5 Pa to 1.3 Pa.
[0027] In a preferred embodiment of the present invention, the process of depositing a conductive layer on both sides of a commercial porous polymer substrate using a chemical vapor deposition method comprises the following steps:
[0028] Using a chemical vapor deposition apparatus and using CH4, AlCl3, MoCl5, C8H 24N4Sn, TiCl4(THF)2, TiCl4, Ti[N(CH3)2]4, C3H9In, In(NO3)3H2O or SnCl4 is used as precursor A, and one of NH3, O2, H2 and H2O is used as carrier gas for depositing a conductive layer, wherein the protective gas is introduced together with the precursor A, the deposition temperature is 150℃~600℃, the deposition time is 60min~720min, and the reaction chamber pressure is 4Tor~8Tor.
[0029] In a preferred embodiment of the present invention, the process of depositing a conductive layer on both sides of a commercial porous polymer substrate film using a magnetron sputtering method comprises the following steps:
[0030] A radio frequency magnetron sputtering method is used and carbon black, Al, Sn, Fe, Zn, Pt, Ni, Cu, Co, Au, Ag, Pb, Ti, Mo, TiN, MoN, SnO2 or ITO is used as a target material for depositing a conductive layer, wherein the sputtering atmosphere is an argon atmosphere, the argon flow rate is 10sccm to 1000sccm, the sputtering power is 100W to 500W, the sputtering voltage is 50V to 500V, and the sputtering temperature is 50°C to 800°C.
[0031] In a preferred embodiment of the present invention, the step of depositing an insulating layer on the outer side of the conductive modified diaphragm by atomic layer deposition comprises the following steps:
[0032] The precursors for forming the insulating layer by reaction are introduced into the atomic layer deposition reaction chamber to deposit the conductive layer. The precursors include precursor A and precursor B. Specifically, an atomic layer deposition apparatus is used and C3H9Al, Al(TMHD)3, AlEt3, AlH3DMEA, Al2(NMe2)6, C 33 H 57 AlO6, Al(acac)3, C4H 13 AlO, Al(OEt)3, Al(OiPr)3, AlMe2OiPr, AlCl3, AlI3, C 12 H 16 Zr, C 22 H 36 Zr, C 20 H 32 Zr 10 、C8H 24 N4Zr、C4H 11 NZr, CpZr(NMe2)3, C8H 20 O4Zr、C 16 H 36 O4Zr、C 44 H 76 O8Zr、C 18 H 28 OZr、C12 H 28 O4Zr.C3H8O、C 16 H 36 O4Zr、Zr(CpMe)2(OMe)Me、C 20 H 16 F 12 O8Zr、ZrCl4、C 12 H 12 Ti、Ti(NEt2)4、Ti(NMe2)4、C3H9NTi、C 16 H 33 N3Ti、C 12 H 28 O4Ti、C 10 H 15. C3H9O3Ti、C 10 H 15. C3H9O3Ti、C 16 H 36 O4Ti、Ti(OEt)4、C 10 H 15 Cl3Ti、TiCl4、HfCp2Me2、C 20 H 32 Hf 10 、C 16 H 40 HfN4、C8H 24 HfN4、C 12 H 32 HfN4、CpHf(NMe2)3、C8H 20 HfO4、C 16 H 36 HfO4、C 44 H 76 HfO8、C 20 H 28 HfO8、C 16 H 36 HfO4、HfCp2Cl2、C 16 H 22 Cl2Hf 10 、C8H7Cl3Hf、C10H 15 Cl3Hf、C 20 H 30 Cl2Hf 10 、C 14 H 18 Cl2Hf 10 、HfCl4、C4H 12 Si、SiHMe3、SiH(NMe2)3、SiH2(NEt2)2、SiH2(NHtBu)2、C6H 18 N2Si、C6H17 NSi、C6H 21 N3Si3、C6H 18 N2Si、C 12 H 32 N4Si、C4H 12 O4Si、C8H 20 O4Si、C6H 18 OSi2, C 15 H 34 O4Si、Si(OEt)4、C4H 14 OSi2, Si(OMe)4, C9H 23 NO3Si, Si(OnBu)4, Si(OtBu)3OH, Si2(NHEt)6, SiCl4, SiBr4, C6H 15 B. C6H 15 BO3, BBr3, Sr(CpiPr3)2, C5HF6O2Sr, C 32 H 60 O9Sr、C 11 H 21 O3Sr、C 24 H 38 Ba 10 , C 20 H 30 Ba, C 10 H 10 BaF7O2、C 10 H 14 BaO4、C 32 H 60 BaO9、C 30 H 56 One or more of BaO8 and Ba(dpm)2 are used as precursor A, and one of NH3, O3 and H2O is used as precursor B to deposit a conductive layer, wherein the sputtering atmosphere is a nitrogen or argon atmosphere, the carrier gas flow rate is 30sccm~800sccm, the precursor introduction time is 0.1s~60s, the diffusion time is 0.1s~60s, and the growth temperature is 100℃~1000℃.
[0033] In a preferred embodiment of the present invention, the process of depositing an insulating layer on the outer side of the conductive modified diaphragm by physical vapor deposition comprises the following steps:
[0034] A physical vapor deposition apparatus is used and one or more of Si, Al2O3, ZrO2, TiO2, HfO2, SiO2, BN, C3N4, BaTiO3 or SrTiO3 are adopted as coating materials. Argon gas is introduced as protective gas. The deposition temperature is 350°C to 650°C, the deposition time is 60min to 600min, the deposition rate is about 0.2nm / s to 2nm / s, the deposition bias is preferably 25V to 100V, the power is preferably 100W to 200W, the sputtering bias is preferably 25V to 100V, and the sputtering pressure is preferably 0.5Pa to 1.3Pa.
[0035] In a preferred embodiment of the present invention, the process of depositing an insulating layer on the outer side of the conductive modified diaphragm by chemical vapor deposition comprises the following steps:
[0036] Using a chemical vapor deposition (CVD) apparatus and C 12 H 28 O4Ti, TiCl4, Ti(OMe)4, C8H 24 N2Ti, Ti(Me5Cp)(OMe)3, SiCl4, C 18 H 20 O6Si、SiH4、C6H 17 NSi、C9H 27 NSi3, Cl6Si2, C6H 19 N3Si、C5H 14 O2Si、C8H 24 O4Si4、C3H 10 Si、C4H 12 Si、C8H 22 N2Si, C3H9Al, AlCl3, ZrCl4, Zr[N(CH3)(C2H5)]4, Zr[N(CH2CH3)2]4, Zr[N(CH3)2]4, HfCl4, Hf[N(CH3)(C2H5)]4, Hf[N(CH2CH3)2]4, Hf[N(CH3)2]4, BCl3, B2H6, CH3CN, C9H 18 N6, Ba(DPM)2, Ti(OiPr)4, Ba(C 11 H 19 O2)2、C 16 H 30 BaO4、C 28 H 46 Ba、Sr(C 11 H 19One or more of Sr(O2)2 or Sr(DPM)2 is used as a precursor, and one of NH3, O2, N2 and H2O is used as a carrier gas with a flow rate of 2000sccm to 10000sccm for depositing an insulating layer, wherein a protective gas is introduced together with the precursor with a flow rate of 3000sccm to 10000sccm, the deposition temperature is 300℃ to 650℃, the deposition time is 120min to 720min, and the reaction chamber pressure is 5Tor to 8Tor.
[0037] In a preferred embodiment of the present invention, the method of depositing an insulating layer on the outer side of the conductive modified diaphragm by magnetron sputtering comprises the following steps:
[0038] A radio frequency magnetron sputtering method is used and one or more of Si, Al2O3, ZrO2, TiO2, SiO2, BN, C3N4, BaTiO3 or SrTiO3 are used as targets for depositing an insulating layer, wherein the sputtering atmosphere is a nitrogen or argon atmosphere, the gas flow rate is 10sccm to 1000sccm, the sputtering power is 200W to 500W, the sputtering voltage is 50V to 500V, and the sputtering temperature is 50℃ to 800℃.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] In order to reduce the risk of puncture of the diaphragm and improve the stability and safety of the diaphragm, the present invention uses a commercial porous polymer film as the diaphragm matrix, and sequentially wraps a conductive layer and an insulating layer on both sides of the diaphragm matrix. The introduction of a nano-thick conductive layer effectively affects the deposition mode of active ions and charge transfer, and generates a strong uniform electric field and thermal field at the diaphragm / electrolyte / metal negative electrode interface, which can not only further promote the uniform and orderly distribution of active ions and charge transfer, but also play a role in heat diffusion. While improving the electrochemical reaction kinetics, it promotes the uniform deposition of active ions on the metal surface, uniformly distributes the heat on the metal surface, inhibits dendrite growth, and constructs a stable metal interface, thereby achieving the purpose of safe long-term battery circulation and improving the coulombic efficiency of the battery. The insulating layer has an electronic insulating effect to prevent the diaphragm electronic conductivity from being too strong, resulting in a short circuit between the positive and negative electrodes. The orderly porous structure and flexibility of the commercial porous polymer film itself are conducive to the assembly of the battery and can reduce the interface resistance.
[0041] The preparation method of the present invention is simple, and the deposition of nano-thick conductive layers and insulating layers can be achieved through a variety of methods. It is easy to control and has excellent performance. It is a high-performance battery separator modification strategy with broad application prospects. It can be widely used in high-energy density metal batteries, and has opened up a new path for the research and development and application of high-performance lithium / sodium / potassium / zinc / aluminum metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1In the figure, (a) is the HRTEM image of the composite membrane prepared in Example 1, and (b) is the element mapping image of the composite membrane prepared in Example 1.
[0043] Figure 2 Long cycle diagram of AIBs assembled with the composite membrane prepared in Example 1 of the present invention and the GF filter membrane of Comparative Example 1.
[0044] Figure 3 Long cycle diagram of NMBs assembled with the composite membrane prepared in Example 4 of the present invention and the GF filter membrane of Comparative Example 1. DETAILED DESCRIPTION
[0045] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention. The experimental methods and detection methods described in the following embodiments are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.
[0046] Example 1
[0047] SnO2 and TiO2 are deposited on both sides of the glass fiber filter membrane in sequence. The specific preparation method is as follows:
[0048] 1) Place the glass fiber filter membrane in a vacuum oven and dry it at 60°C for 12 hours.
[0049] 2) Place the pretreated glass fiber filter membrane into the chamber of the atomic layer deposition instrument for atomic layer deposition of SnO2 thin film. The specific deposition process is: growth temperature is 200℃; precursor is C8H 24 N4Sn,C8H 24 The source temperature of N4Sn is 45℃, the introduction time is 1s, and the diffusion time is 20s; the reactant is O3, the introduction time is 30s, and the diffusion time is 40s; the number of deposition cycles is 75C. After the deposition process is completed, wait for the temperature in the instrument chamber to drop to room temperature, turn over the glass fiber filter membrane with a single-sided conductive layer deposited in the chamber, so that the undeposited side faces upward, and send it into the chamber again for double-sided deposition (the process is the same as above); the thickness of the deposited SnO2 is: 20nm.
[0050] 3) After the temperature of the atomic layer deposition instrument chamber drops to room temperature, continue the atomic layer deposition TiO2 thin film process. The specific deposition process is: growth temperature is 200℃; precursor is C 12 H 28 O4Ti,C 12 H 28The source temperature of O4Ti is 45℃, the introduction time is 2s, and the diffusion time is 30s; the reactant is O3, the introduction time is 2s, and the diffusion time is 40s; the number of deposition cycles is 75C. After the deposition process is completed, wait for the temperature in the instrument chamber to drop to room temperature, turn over the glass fiber filter membrane with a single-sided insulation layer deposited in the chamber, so that the undeposited side faces upward, and send it into the chamber again for double-sided deposition (the process is the same as above); the thickness of the deposited TiO2 film is 20nm.
[0051] 4) After the temperature of the atomic layer deposition instrument chamber drops to room temperature, the glass fiber filter membrane after double-sided deposition is taken out to obtain a metal battery composite diaphragm - GF@SnO2@TiO2, which can inhibit dendrite growth and has an inner shell SnO2 conductive layer and an outer shell TiO2 insulating layer uniformly formed on the surface of the pretreated glass fiber filter membrane.
[0052] Example 2
[0053] TiN film and BaTiO3 film are deposited on both sides of the glass fiber filter membrane respectively. The specific preparation method is as follows:
[0054] 1) Place the glass fiber filter membrane in a vacuum oven and dry it at 60°C for 12 hours.
[0055] 2) Place the pretreated glass fiber filter membrane into the chamber of the atomic layer deposition instrument to carry out the atomic layer deposition TiN thin film process. The specific deposition process is: the growth temperature is 300℃; the precursor is C8H 24 N2Ti,C8H 24 The source temperature of N2Ti is 45℃, the introduction time is 1s, and the diffusion time is 30s; the reactant is NH3, the introduction time is 20s, and the diffusion time is 30s; the number of deposition cycles is 75C. After the deposition process is completed, wait for the temperature in the instrument chamber to drop to room temperature, turn over the glass fiber filter membrane with a single-sided conductive layer deposited in the chamber, so that the undeposited side faces up, and send it into the chamber again for double-sided deposition (the process is the same as above); the thickness of the deposited TiN film is 20nm.
[0056] 3) After the temperature of the atomic layer deposition instrument chamber drops to room temperature, continue the atomic layer deposition BaTiO3 thin film process. The specific deposition process is: growth temperature is 225℃; precursor is C 12 H 28 O4Ti and C 28 H 46 Ba, C 12 H 28 The source temperature of O4Ti is 35℃, C 28 H 46 The source temperature of Ba is 145℃, C 12 H 28 O4Ti and C 28 H46 Ba is introduced for 2s and diffused for 15s; the reactant is H2O, which is introduced for 1s and diffused for 15s; C 12 H 28 O4Ti and C 28 H 46 The unit cycle number of Ba is 4:3 deposition ratio, and the deposition cycle is 100C. After the deposition process is completed, wait for the temperature in the instrument chamber to drop to room temperature, turn over the glass fiber filter membrane with a single-sided conductive layer deposited in the chamber, so that the non-deposited side faces upward, and send it into the chamber again for double-sided deposition (the process is the same as above); the thickness of the deposited BaTiO3 film is 20nm.
[0057] 4) After the temperature of the atomic layer deposition (ALD) instrument cavity drops to room temperature, the glass fiber filter membrane after double-sided deposition is taken out to obtain a metal battery composite diaphragm - GF@TiN@BaTiO3, which can inhibit dendrite growth and has an inner shell TiN conductive layer and an outer shell BaTiO3 insulating layer uniformly formed on the surface of the pretreated glass fiber filter membrane.
[0058] Example 3
[0059] MoN film and BN film are sequentially deposited on both sides of the glass fiber filter membrane. The specific preparation method is as follows:
[0060] 1) Place the glass fiber filter membrane in a vacuum oven and dry it at 60°C for 12 hours.
[0061] 2) Place the pretreated glass fiber filter membrane into the atomic layer deposition chamber for atomic layer deposition of MoN thin film. The specific deposition process is: growth temperature is 225℃; the precursor is C6O6Mo, the source temperature of C6O6Mo is 20℃, the introduction time is 1s, and the diffusion time is 30s; the reactant is NH3, the introduction time is 5s, and the diffusion time is 20s; the number of deposition cycles is 75C. After the deposition process is completed, wait for the temperature in the chamber of the instrument to drop to room temperature, turn over the glass fiber filter membrane with a single-sided conductive layer deposited in the chamber, so that the undeposited side faces up, and send it into the chamber again for double-sided deposition (the process is the same as above); the thickness of the deposited MoN film is 20nm.
[0062] 3) After the temperature of the atomic layer deposition instrument chamber drops to room temperature, continue the atomic layer deposition BN film process. The specific deposition process is: growth temperature is 225℃; the precursor is BBr3, the source temperature of BBr3 is 25℃, the BBr3 introduction time is 0.1s, and the diffusion time is 7s; the reactant is NH3, the introduction time is 5s, and the diffusion time is 5s; the number of deposition cycles is 75C. After completing the deposition process, wait for the temperature in the instrument chamber to drop to room temperature, turn over the glass fiber filter membrane with a single-sided conductive layer deposited in the chamber, so that the undeposited side faces up, and send it into the chamber again for double-sided deposition (the process is the same as above); the thickness of the deposited BN film is 20nm.
[0063] 4) After the temperature of the atomic layer deposition instrument chamber drops to room temperature, the glass fiber filter membrane after double-sided deposition is taken out to obtain a metal battery composite diaphragm - GF@MoN@BN, which can inhibit dendrite growth and has an inner shell MoN conductive layer and an outer shell BN insulating layer uniformly formed on the surface of the pretreated glass fiber filter membrane.
[0064] Example 4
[0065] Al film and Al2O3 film are sequentially deposited on both sides of the glass fiber filter membrane. The specific preparation method is as follows:
[0066] 1) Place the glass fiber filter membrane in a vacuum oven and dry it at 60°C for 12 hours.
[0067] 2) Place the pretreated glass fiber filter membrane into the reaction chamber of the physical vapor deposition instrument to deposit Al thin film. The specific deposition process is: using Al material, the sputtering atmosphere is argon atmosphere, the argon flow rate is 20sccm, the DC sputtering power is 120W, the deposition temperature is 200℃, the sputtering pressure is 0.5Pa, the sputtering bias is 50V, the deposition rate is about 0.8nm / s, and the deposition time is 2h. The thickness of the deposited Al film is 16nm.
[0068] 3) After the temperature of the reaction chamber of the physical vapor deposition instrument drops to room temperature, continue the physical vapor deposition Al2O3 film process. The specific deposition process is: using Al2O3 material, the sputtering atmosphere is argon atmosphere, the argon flow rate is 50sccm, the DC sputtering power is 200W, the deposition temperature is 400℃, the sputtering pressure is 0.8Pa, the sputtering bias is 100V, the deposition rate is about 0.5nm / s, and the deposition time is 5h. The thickness of the deposited Al2O3 film is 18nm.
[0069] 4) After the temperature of the physical vapor deposition instrument cavity drops to room temperature, the deposited glass fiber filter membrane is taken out to obtain a metal battery composite diaphragm - GF@Al@Al2O3 which can inhibit dendrite growth and has an inner shell Al conductive layer and an outer shell Al2O3 insulating layer uniformly formed on the surface of the pretreated glass fiber filter membrane.
[0070] Example 5
[0071] TiN film and BN film are sequentially deposited on both sides of the glass fiber filter membrane. The specific preparation method is as follows:
[0072] 1) Place the glass fiber filter membrane in a vacuum oven and dry it at 60°C for 12 hours.
[0073] 2) Place the pretreated glass fiber filter membrane into the reaction chamber of the physical vapor deposition instrument to deposit the TiN thin film. The specific deposition process is: using TiN material, the sputtering atmosphere is argon atmosphere, the argon flow rate is 50sccm, the DC sputtering power is 150W, the deposition temperature is 400℃, the sputtering pressure is 0.5Pa, the sputtering bias is 90V, the deposition rate is about 0.2nm / s, and the deposition time is 6h. The thickness of the deposited TiN film is 14nm.
[0074] 3) After the temperature of the reaction chamber of the physical vapor deposition instrument drops to room temperature, continue the physical vapor deposition BN film process. The specific deposition process is: using BN material, the sputtering atmosphere is argon atmosphere, the argon flow rate is 80sccm, the DC sputtering power is 180W, the deposition temperature is 350℃, the sputtering pressure is 0.6Pa, the sputtering bias is 120V, the deposition rate is about 0.6nm / s, and the deposition time is 6h. The thickness of the deposited BN film is 16nm.
[0075] 4) After the temperature of the physical vapor deposition instrument chamber drops to room temperature, the deposited glass fiber filter membrane is taken out to obtain a metal battery composite diaphragm - GF@TiN@BN, which can inhibit dendrite growth and has an inner shell TiN conductive layer and an outer shell BN insulating layer uniformly formed on the surface of the pretreated glass fiber filter membrane.
[0076] Example 6
[0077] ITO film and BaTiO3 film are sequentially deposited on the glass fiber filter membrane. The specific preparation method is as follows:
[0078] 1) Place the glass fiber filter membrane in a vacuum oven and dry it at 60°C for 12 hours.
[0079] 2) Place the pretreated glass fiber filter membrane into the reaction chamber of the physical vapor deposition instrument to deposit the ITO thin film. The specific deposition process is: using ITO material, the sputtering atmosphere is argon atmosphere, the argon flow rate is 120sccm, the DC sputtering power is 120W, the deposition temperature is 450℃, the sputtering pressure is 0.8Pa, the sputtering bias is 120V, the deposition rate is about 0.5nm / s, and the deposition time is 4h. The thickness of the deposited ITO film is 20nm.
[0080] 3) After the temperature of the reaction chamber of the physical vapor deposition instrument drops to room temperature, continue the physical vapor deposition BaTiO3 thin film process. The specific deposition process is: using BaTiO3 material, the sputtering atmosphere is argon atmosphere, the argon flow rate is 140sccm, the DC sputtering power is 150W, the deposition temperature is 400℃, the sputtering pressure is 0.6Pa, the sputtering bias is 90V, the deposition rate is about 0.4nm / s, and the deposition time is 8h. The thickness of the deposited BaTiO3 film is 20nm.
[0081] 4) After the temperature of the physical vapor deposition instrument cavity drops to room temperature, the deposited glass fiber filter membrane is taken out to obtain a metal battery composite diaphragm - GF@ITO@BaTiO3, which can inhibit dendrite growth and has an inner shell ITO conductive layer and an outer shell BaTiO3 insulating layer uniformly formed on the surface of the pretreated glass fiber filter membrane.
[0082] Example 7
[0083] SnO2 film and SiO2 film are sequentially deposited on both sides of the glass fiber filter membrane. The specific preparation method is as follows:
[0084] 1) Place the glass fiber filter membrane in a vacuum oven and dry it at 60°C for 12 hours.
[0085] 2) Place the pretreated glass fiber filter into the reaction chamber of a chemical vapor deposition instrument to deposit SnO2 thin film. The specific deposition process is: heat the reaction chamber to 600°C, introduce H2 into the reaction chamber, the hydrogen flow rate is 200 sccm, use nitrogen (Ar) as a carrier gas to bring SnCl2 into the reaction chamber, the nitrogen flow rate is 3000 sccm, and the SnCl2 flow rate is 2g min ~1 The deposition temperature is 300℃, the deposition time is 60min, and the pressure in the reaction chamber is 6 Torr. The thickness of the deposited SnO2 film is 15nm.
[0086] 3) After the temperature of the chemical vapor deposition instrument chamber drops to room temperature, continue the chemical vapor deposition SiO2 thin film process. The specific deposition process is: heat the reaction chamber to 450°C, introduce O2 into the reaction chamber, the oxygen flow rate is 2000sccm, and use nitrogen (N2) as the carrier gas to transfer C8H 20 O4Si was introduced into the reaction chamber, the nitrogen flow rate was 3000sccm, C8H 20 The flow rate of O4Si was 2 g min ~1 The deposition temperature is 450℃, the deposition time is 360min, and the pressure of the reaction chamber is 6 Tor; the thickness of the deposited SiO2 film is 18nm.
[0087] 4) After the temperature of the chemical vapor deposition instrument chamber drops to room temperature, the deposited glass fiber filter membrane is taken out to obtain a metal battery composite diaphragm - GF@SnO2@SiO2, which can inhibit dendrite growth and has an inner shell SnO2 conductive layer and an outer shell SiO2 insulating layer uniformly formed on the surface of the pretreated glass fiber filter membrane.
[0088] Example 8
[0089] Mo film and TiO2 film are sequentially deposited on both sides of the glass fiber filter membrane. The specific preparation method is as follows:
[0090] 1) Place the glass fiber filter membrane in a vacuum oven and dry it at 60°C for 12 hours.
[0091] 2) Place the pretreated glass fiber filter membrane into the reaction chamber of the chemical vapor deposition instrument to deposit the Mo thin film. The specific deposition process is: heat the reaction chamber to 50°C, introduce argon (Ar) as a carrier gas into the reaction chamber to bring C6O6Mo into the reaction chamber, the argon flow rate is 1000sccm, and the C6O6Mo flow rate is 0.6g min ~1 The deposition temperature is 150°C, the deposition time is 240 min, and the pressure in the reaction chamber is 4 Torr. The thickness of the deposited Mo film is 19 nm.
[0092] 3) After the temperature of the chemical vapor deposition instrument chamber drops to room temperature, continue the chemical vapor deposition TiO2 thin film process. The specific deposition process is: heat the reaction chamber to 300°C, introduce O2 into the reaction chamber, the oxygen flow rate is 2000sccm, and use argon (Ar) as the carrier gas to pass C 12 H 28 O4Ti was introduced into the reaction chamber, and the flow rate of argon was 3000sccm. 12 H 28 The flow rate of O4Ti was 2 g min ~1 The deposition temperature is 300℃, the deposition time is 360min, and the pressure of the reaction chamber is 6 Torr. The thickness of the deposited TiO2 film is 21nm.
[0093] 4) After the temperature of the chemical vapor deposition instrument chamber drops to room temperature, the deposited glass fiber filter membrane is taken out to obtain a metal battery composite diaphragm - GF@Mo@TiO2, which can inhibit dendrite growth and has an inner shell Mo conductive layer and an outer shell TiO2 insulating layer uniformly formed on the surface of the pretreated glass fiber filter membrane.
[0094] Example 9
[0095] TiN film and BN film are sequentially deposited on the glass fiber filter membrane. The specific preparation method is as follows:
[0096] 1) Place the glass fiber filter membrane in a vacuum oven and dry it at 60°C for 12 hours.
[0097] 2) Place the pretreated glass fiber filter into the reaction chamber of the chemical vapor deposition instrument to deposit the TiN thin film. The specific deposition process is: heat the reaction chamber to 850°C, introduce NH3 into the reaction chamber, the flow rate of ammonia is 2000sccm, use argon (Ar) as a carrier gas to bring TiCl4 into the reaction chamber, the flow rate of argon is 3000sccm, and the flow rate of TiCl4 is 2g min ~1 The deposition temperature is 450°C, the deposition time is 300 min, and the pressure in the reaction chamber is 7.5 Torr. The thickness of the deposited TiN film is 16 nm.
[0098] 3) After the temperature of the chemical vapor deposition instrument chamber drops to room temperature, continue the chemical vapor deposition BN film process. The specific deposition process is: heat the reaction chamber to 200°C, introduce NH3 into the reaction chamber, the oxygen flow rate is 2000sccm, use argon (Ar) as a carrier gas to bring BCl3 into the reaction chamber, the argon flow rate is 3000sccm, and the BCl3 flow rate is 2g min ~1 The deposition temperature is 650℃, the deposition time is 360min, and the pressure of the reaction chamber is 5 Torr. The thickness of the deposited BN film is 19nm.
[0099] 4) After the temperature of the chemical vapor deposition (CVD) instrument cavity drops to room temperature, the deposited glass fiber filter membrane is taken out to obtain a metal battery composite diaphragm - GF@TiN@BN, which can inhibit dendrite growth and has an inner shell TiN conductive layer and an outer shell BN insulating layer uniformly formed on the surface of the pretreated glass fiber filter membrane.
[0100] Example 10
[0101] C film and SiO2 film are sequentially deposited on both sides of the glass fiber filter membrane. The specific preparation method is as follows:
[0102] 1) Place the glass fiber filter membrane in a vacuum oven and dry it at 60°C for 12 hours.
[0103] 2) Place the pretreated glass fiber filter membrane into the reaction chamber of the magnetron sputtering instrument to deposit the C film. The specific deposition process is: using carbon black target material, the sputtering atmosphere is argon atmosphere, the argon flow rate is 30-50sccm, the sputtering power is 300-400W, the sputtering voltage is 100-200V, and the sputtering temperature is 100-200℃. It should be noted that during the magnetron sputtering process, the above parameters are not constant values, but fluctuate within the above ranges. The thickness of the deposited C film is 25nm.
[0104] 3) After the temperature of the reaction chamber of the magnetron sputtering instrument drops to room temperature, the magnetron sputtering SiO2 film process is continued. The specific deposition process is: using SiO2 target material, the sputtering atmosphere is argon atmosphere, the argon flow rate is 50-100sccm, the sputtering power is 200-500W, the sputtering voltage is 60-150V, and the sputtering temperature is 100-450℃. It should be noted that during the magnetron sputtering process, the above parameters are not constant values, but fluctuate within the above ranges. The thickness of the deposited SiO2 film is 25nm.
[0105] 4) After the temperature of the magnetron sputtering instrument cavity drops to room temperature, the sputtered glass fiber filter membrane is taken out to obtain a metal battery composite diaphragm - GF@C@SiO2, which can inhibit dendrite growth and has an inner shell C conductive layer and an outer shell SiO2 insulating layer uniformly formed on the surface of the pretreated glass fiber filter membrane.
[0106] Embodiment 11
[0107] ITO film and BaTiO3 film are sequentially deposited on both sides of the glass fiber filter membrane. The specific preparation method is as follows:
[0108] 1) Place the glass fiber filter membrane in a vacuum oven and dry it at 60°C for 12 hours.
[0109] 2) Place the pretreated glass fiber filter membrane into the reaction chamber of the magnetron sputtering instrument to deposit the ITO thin film. The specific deposition process is: using ITO target material, the sputtering atmosphere is argon atmosphere, the argon flow rate is 10-30sccm, the sputtering power is 200-400W, the sputtering voltage is 100-200V, and the sputtering temperature is 200-650℃. It should be noted that during the magnetron sputtering process, the above parameters are not constant values, but fluctuate within the above ranges. The thickness of the deposited ITO film is 25nm.
[0110] 3) After the temperature of the reaction chamber of the magnetron sputtering instrument drops to room temperature, continue the magnetron sputtering BaTiO3 thin film process. The specific deposition process is: using BaTiO3 target material, the sputtering atmosphere is argon atmosphere, the argon flow rate is 50-200sccm, the sputtering power is 200-500W, the sputtering voltage is 100-250V, and the sputtering temperature is 450-750℃. It should be noted that during the magnetron sputtering process, the above parameters are not constant values, but fluctuate within the above ranges. The thickness of the deposited BaTiO3 film is 20nm.
[0111] 4) After the temperature of the magnetron sputtering instrument cavity drops to room temperature, the sputtered glass fiber filter membrane is taken out to obtain a metal battery composite diaphragm - GF@ITO@BaTiO3, which can inhibit dendrite growth and has an inner shell ITO conductive layer and an outer shell BaTiO3 insulating layer uniformly formed on the surface of the pretreated glass fiber filter membrane.
[0112] Example 12
[0113] TiN film and BN film are sequentially deposited on both sides of the glass fiber filter membrane. The specific preparation method is as follows:
[0114] 1) Place the glass fiber filter membrane in a vacuum oven and dry it at 60°C for 12 hours.
[0115] 2) Place the pretreated glass fiber filter membrane into the reaction chamber of the magnetron sputtering instrument to deposit the TiN film. The specific deposition process is: using TiN target material, the sputtering atmosphere is argon atmosphere, the argon flow rate is 20-50sccm, the sputtering power is 100-200W, the sputtering voltage is 100-300V, and the sputtering temperature is 400-600℃. It should be noted that during the magnetron sputtering process, the above parameters are not constant values, but fluctuate within the above ranges. The thickness of the deposited TiN film is 23nm.
[0116] 3) After the temperature of the reaction chamber of the magnetron sputtering instrument drops to room temperature, continue the magnetron sputtering BN film process. The specific deposition process is: using BN target material, the sputtering atmosphere is argon atmosphere, the argon flow rate is 50-200sccm, the sputtering power is 300-500W, the sputtering voltage is 100-200V, and the sputtering temperature is 150-350℃. It should be noted that during the magnetron sputtering process, the above parameters are not constant values, but fluctuate within the above ranges. The thickness of the deposited BN film is 26nm.
[0117] 4) After the temperature of the magnetron sputtering instrument cavity drops to room temperature, the sputtered glass fiber filter membrane is taken out to obtain a metal battery composite diaphragm - GF@TiN@BN, which can inhibit dendrite growth and has an inner shell TiN conductive layer and an outer shell BN insulating layer uniformly formed on the surface of the pretreated glass fiber filter membrane.
[0118] Comparative Example 1
[0119] Glass fiber filter membrane without conductive layer and insulating layer deposited, original GF membrane.
[0120] The composite membranes prepared in Examples 1 to 12 and the original GF membrane of Comparative Example 1 were assembled into Al / / Al symmetric cells of aluminum ion batteries (AIBs), and the effects are shown in Table 1:
[0121] Table 1 Effect data of composite membranes of Examples 1 to 12 and original GF membrane of Comparative Example 1 assembled into Al symmetric cells
[0122]
[0123]
[0124] The charge and discharge test results in Table 1 show that the polarization potential of the battery assembled with the composite membranes of Examples 1 to 12 is lower than that of the battery assembled with the GF membrane, which further indicates that the composite membrane has the function of reducing the polarization voltage and stabilizing the Al metal deposition and stripping behavior.
[0125] Similarly, when Examples 1 to 12 are used in sodium, potassium, magnesium, zinc, and calcium ion batteries, the polarization voltage is also reduced, and the metal deposition and stripping behavior is stabilized.
[0126] Figure 1 (a) is the HRTEM image of the composite membrane prepared in Example 1, and (b) is the element mapping image of the composite membrane prepared in Example 1. It can be clearly seen that the SnO2 and TiO2 nanolayers are successfully introduced, and the introduced SnO2 conductive layer and TiO2 insulating layer are uniformly and densely wrapped on the surface of the GF fiber, which is conducive to the generation of uniform electric and thermal fields at the interface of the membrane, achieving the effect of regulating the orderly deposition of the metal negative electrode; the deposition layer is a nanolayer, and the GF fiber structure is not changed, which ensures that the membrane has good electrolyte absorption and retention rate and uniform ion channels, and realizes good transmission of active ions.
[0127] Figure 2 The results show that when the GF@SnO2@TiO2 membrane prepared in Example 1 is assembled into aluminum ion batteries (AIBs), the battery can stably cycle more than 200 times at a current density of 0.2A / g, the coulombic efficiency remains above 98%, and the discharge specific capacity of 80.9mAh / g is also much higher than the 68.5mAh / g of the GF membrane assembled battery, further proving that the GF@SnO2@TiO2 membrane has good ionic conductivity and porosity, and can meet the charging and discharging requirements of aluminum ion batteries (AIBs).
[0128] Figure 3The results show that when the prepared GF@Al@Al2O3 membrane is assembled into a sodium metal battery (NMBs), the capacity retention rate of 200 cycles of long cycle test at a current density of 1C=117mA / g reaches 98%, which is much higher than the 90.5% of the GF assembled battery, showing excellent cycle stability. The same effect is also applicable to sodium, potassium, magnesium, zinc, and calcium ion batteries. The membrane can be adapted to various types of metal batteries to achieve safe and effective long-term battery cycles. It has certain versatility and is a metal battery composite membrane that can inhibit dendrite growth and has broad application prospects.
[0129] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, they are also intended to be included.
Claims
1. A metal battery composite diaphragm, characterized in that: It comprises a diaphragm substrate, a conductive layer and an insulating layer, wherein the conductive layers are deposited on both sides of the diaphragm substrate, and the insulating layer is deposited on the outer side of the conductive layer; The conductive layer is TiN, MoN, SnO2, ITO, Al, Sn, Fe, Zn, Pt, Ni, Cu, Co, Au, Ag, Pb, Ti, Mo or C; The insulating layer is Al2O3, ZrO2, TiO2, HfO2, SiO2, BN, C3N4, BaTiO3, SrTiO3 or Si; The thickness of the conductive layer is 1 nm to 50 nm, and the thickness of the insulating layer is 1 nm to 50 nm.
2. The method for preparing a metal battery composite diaphragm according to claim 1, characterized in that: The following steps are involved: The diaphragm substrate is cleaned and dried; Using atomic layer deposition, physical vapor deposition, chemical vapor deposition or magnetron sputtering, depositing a conductive layer on both sides of the treated membrane substrate to obtain a conductive modified membrane; An insulating layer is deposited on the outer side of the conductive modified diaphragm by atomic layer deposition, physical vapor deposition, chemical vapor deposition or magnetron sputtering to obtain a metal battery composite diaphragm.
3. The preparation method according to claim 2, characterized in that: When a conductive layer is deposited on both sides of the treated diaphragm substrate using an atomic layer deposition method, the conductive layer is TiN, MoN, SnO2 or ITO; the atomic layer deposition method includes the following steps: The precursors that react to generate a conductive layer of TiN, MoN, SnO2 or ITO are introduced into the reaction chamber of an atomic layer deposition instrument to deposit a conductive layer, wherein the sputtering atmosphere is a nitrogen or argon atmosphere, the carrier gas flow rate is 30sccm to 800sccm, the precursor introduction time is 0.1s to 60s, the diffusion time is 0.1s to 60s, and the growth temperature is 100°C to 1000°C.
4. The preparation method according to claim 2, characterized in that: When a conductive layer is deposited on both sides of the treated diaphragm substrate by physical vapor deposition, the conductive layer is Al, Sn, Fe, Zn, Pt, Ni, Cu, Co, Au, Ag, Pb, Ti, Mo, TiN, MoN, SnO2 or ITO; the physical vapor deposition method includes the following steps: A physical vapor deposition apparatus is used and Al, Sn, Fe, Zn, Pt, Ni, Cu, Co, Au, Ag, Pb, Ti, Mo, TiN, MoN, SnO2 or ITO is used as the coating material. Argon is introduced as the protective gas. The deposition temperature is 200°C to 650°C, the deposition time is 60min to 600min, the deposition rate is 0.2nm / s to 2nm / s, the deposition bias is 25V to 100V, the power is 100W to 200W, the sputtering bias is 25V to 120V, and the sputtering pressure is 0.5Pa to 1.3Pa.
5. The preparation method according to claim 2, characterized in that: When a conductive layer is deposited on both sides of the treated diaphragm substrate by chemical vapor deposition, the conductive layer is C, Al, Mo, SnO2, TiN or ITO; the chemical vapor deposition method includes the following steps: Using a chemical vapor deposition apparatus and using CH4, AlCl3, MoCl5, C8H 24 One or more of N4Sn, TiCl4(THF)2, TiCl4, Ti[N(CH3)2]4, C3H9In, In(NO3)3H2O and SnCl4 are used as precursors, and one of NH3, O2, H2 and H2O is used as a carrier gas to deposit a conductive layer; the protective gas is introduced together with the precursor, the deposition temperature is 150℃~600℃, the deposition time is 60min~720min, and the reaction chamber pressure is 4Tor~8Tor.
6. The preparation method according to claim 2, characterized in that: When a conductive layer is deposited on both sides of a treated diaphragm substrate by magnetron sputtering, the conductive layer is C, Al, Sn, Fe, Zn, Pt, Ni, Cu, Co, Au, Ag, Pb, Ti, Mo, TiN, MoN, SnO2 or ITO; the magnetron sputtering method includes the following steps: A radio frequency magnetron sputtering method is used and carbon black, Al, Sn, Fe, Zn, Pt, Ni, Cu, Co, Au, Ag, Pb, Ti, Mo, TiN, MoN, SnO2 or ITO is used as a target material for depositing a conductive layer, wherein the sputtering atmosphere is an argon atmosphere, the argon flow rate is 10sccm to 1000sccm, the sputtering power is 100W to 500W, the sputtering voltage is 50V to 500V, and the sputtering temperature is 50°C to 800°C.
7. The preparation method according to claim 2, characterized in that: When an insulating layer is deposited on the outer side of a conductive modified diaphragm by atomic layer deposition, the insulating layer is Al2O3, ZrO2, TiO2, HfO2, SiO2, BN, C3N4, BaTiO3 or SrTiO3; the atomic layer deposition method includes the following steps: The precursor for generating an insulating layer by reaction is introduced into an atomic layer deposition reaction chamber to deposit the insulating layer, wherein the sputtering atmosphere is a nitrogen or argon atmosphere, the carrier gas flow rate is 30sccm to 800sccm, the introduction time of the precursor is 0.1s to 60s, the diffusion time is 0.1s to 60s, and the growth temperature is 100°C to 1000°C.
8. The preparation method according to claim 2, characterized in that: When the insulating layer is deposited on the outer side of the conductive modified diaphragm by physical vapor deposition, the insulating layer is Si, Al2O3, ZrO2, TiO2, HfO2, SiO2, BN, C3N4, BaTiO3 or SrTiO3; the physical vapor deposition method includes the following steps: A physical vapor deposition apparatus is used and an insulating layer material is adopted as the coating material. Argon gas is introduced as the protective gas. The deposition temperature is 350°C to 650°C, the deposition time is 60min to 600min, the deposition rate is 0.2nm / s to 2nm / s, the deposition bias is 25V to 100V, the power is 100W to 200W, the sputtering bias is 25V to 100V, and the sputtering pressure is 0.5Pa to 1.3Pa.
9. The preparation method according to claim 2, characterized in that: When the insulating layer is deposited on the outer side of the conductive modified diaphragm by chemical vapor deposition, the insulating layer is Al2O3, ZrO2, TiO2, SiO2, HfO2, BN, C3N4, BaTiO3 or SrTiO3; the chemical vapor deposition method includes the following steps: Using a chemical vapor deposition system and C 12 H 28 O4Ti, TiCl4, Ti(OMe)4, C8H 24 N2Ti, Ti(Me5Cp)(OMe)3, SiCl4, C 18 H 20 O6Si、SiH4、C6H 17 NSi、C9H 27 NSi3, Cl6Si2, C6H 19 N3Si、C5H 14 O2Si、C8H 24 O4Si4、C3H 10 Si、C4H 12 Si、C8H 22 N2Si, C3H9Al, AlCl3, ZrCl4, Zr[N(CH3)(C2H5)]4, Zr[N(CH2CH3)2]4, Zr[N(CH3)2]4, HfCl4, Hf[N(CH3)(C2H5)]4, Hf[N(CH2CH3)2]4, Hf[N(CH3)2]4, BCl3, B2H6, CH3CN, C9H 18 N6, Ba(DPM)2, Ti(OiPr)4, Ba(C 11 H 19 O2)2、C 16 H 30 BaO4、C 28 H 46 Ba、Sr(C 11 H 19 One or more of O2)2 and Sr(DPM)2 are used as precursors, one of NH3, O2, N2 and H2O is used as carrier gas, and the flow rate is 2000sccm~10000sccm, which is used to deposit the insulating layer. The protective gas is introduced together with the precursor, and the flow rate is 3000sccm~10000sccm. The deposition temperature is 300℃~650℃, the deposition time is 120min~720min, and the pressure of the reaction chamber is 5Tor~8Tor; When the insulating layer is deposited on the outer side of the conductive modified diaphragm by magnetron sputtering, the insulating layer is Si, Al2O3, ZrO2, TiO2, SiO2, BN, C3N4, BaTiO3 or SrTiO3, and the magnetron sputtering method includes the following steps: A radio frequency magnetron sputtering method is used and Si, Al2O3, ZrO2, TiO2, SiO2, BN, C3N4, BaTiO3 or SrTiO3 is used as a target material for depositing an insulating layer. The sputtering atmosphere is a nitrogen or argon atmosphere, the gas flow rate is 10sccm to 1000sccm, the sputtering power is 200W to 500W, the sputtering voltage is 50V to 500V, and the sputtering temperature is 50℃ to 800℃.
10. Use of the metal battery composite separator according to claim 1 in metal batteries.
Citation Information
Cited By
Preparation method of indium-based coating composite diaphragm for aqueous zinc ion battery
CN120341499A
Aqueous zinc ion battery indium-based coating composite diaphragm and preparation method thereof
CN120341499B
